Crafting Project Managers' Careers: Integrating the Fields of Careers and Project Management. Issue 2 (April 2020) - Akkermans, Jos; Keegan, Anne; Huemann, Martina; Ringhofer, Claudia
Project managers experience unique careers that are not yet sufficiently understood, and more people than ever before are pursuing such careers. The research on project management and careers is therefore urgently needed in order to better understand the processes and systems shaping the careers of project managers. We address this gap by reviewing several key career theories and constructs and examining how these are mobilized to understand project managers' careers in existing research. Our main conclusion is that boundaryless career theory has been the dominant career perspective in project management research, whereas other career theories—specifically protean career theory, social cognitive career theory, career construction theory, and sustainable career theory—are far less often mobilized as a basis for studies. We also find that some of the most popular constructs in careers research, such as career success and employability, have been used in recent project management research. However, their use in these studies is often implicit and does not necessarily leverage existing work from the careers field. We argue that there is strong potential for further and more systematic integration between project management and careers research in order to enrich both fields, and we offer a research agenda as a starting point.